Concentration of UHCL1 in the Serum of Children with Acute Appendicitis, Before and After Surgery, and Its Correlation with CRP and Prealbumin. (4th March 2018) - Matuszczak, Ewa; Tylicka, Marzena; Dębek, Wojciech; Tokarzewicz, Anna; Gorodkiewicz, Ewa; Hermanowicz, Adam
ABSTRACT: Ubiquitin-mediated protein degradation plays a crucial role in various cellular processes, including signal transduction, cell differentiation, and stress response. Ubiquitin C-terminal hydrolase 1 (UCHL1) is a unique deubiquitinating enzyme that has both hydrolase and ligase activities. The aim of this study was the determination of UCHL1 concentration in serum of children with appendicitis, before and after the surgery. Material and methods: 42 children with acute appendicitis, who were managed at the Pediatric Surgery Department, between 2013 and 2014, were randomly included into the study (age 9 months up to 14 years, mean age 2.5 + 1 years). There were 15 girls and 27 boys. 18 healthy, age-matched subjects, admitted for planned surgeries served as controls. Exclusion criteria were: severe preexisting infections, immunological or cardiovascular diseases that required long-term medication, and complicated cases of appendicitis with perforation of appendix and/or peritonitis. Results: The UCHL1 concentrations in the blood plasma of patients with acute appendicitis, were highest before the surgery, and were above the range of concentrations measured in controls, the difference was statistically significant. The UCHL1 concentration measured 24 and 72 h after the operation, slowly decreased over time, and still did not reach the normal range, when compared with the concentration measured in controls ( p < 0.05). Conclusions: UCHL1 concentration may reflect the metabolic response to acute state inflammation, and the process of gradual ebbing of the inflammation. The method of operation—classic open appendectomy, or laparoscopic appendectomy, does not influence the general trend in UCHL1 concentration in children with appendicitis. There is strong negative correlation between prealbumin and UCHL1 concentrations.